Editoriales independientes y prácticas de lectura en Latinoamérica. - SÁNCHEZ, CAROLINA; LAWRENCE, JEFFREY (Revista de Estudios Hispánicos, 2025)
This article revolves around statements by a variety of publishers on the role of independent presses in fomenting new reading practices, strategies, and tastes in contemporary Latin America. We asked thirteen publishers from throughout the continent (Argentina, Bolivia, Chile, Colombia, Costa Rica, Cuba, México, Perú, and Puerto Rico) to respond to a series of questions about how they conceive of their publishing practices, the methods they use to create and maintain their reading publics, and the economic and political obstacles they face in pursuing their aims. A brief introduction by the compilers situates the publishers’ responses in relation to the changing conditions of the Hispanophone publishing industry and the resurgence of independent presses in Latin America in the early twenty-first century.